The health of nations: A transatlantic trade and investment agenda for better healthcare - Fredrik Erixon; Martina Francesca Ferracane; Erik Van der Marel (European Centre for International Political Economy (ECIPE), 2015)
Today, increases in the demand for healthcare are driving European governments to look for ways to control growth in healthcare expenditures and at the same time improve health outcomes. Consideration of ways to enhance trade in healthcare goods and services is important for governments as they struggle to find resources to finance this increasing demand for healthcare.
Keywords: 330